Troubling the Functional/Dysfunctional Family Binary Through the Articulation of Functional Family Estrangement. Issue 3 (27th May 2017) - Allen, Jordan; Moore, Julia
Abstract : Critical perspectives remain largely absent from the study of family communication. To interrogate the power of discourse to construct knowledges about how family is and should be, we drew on Judith Butler's poststructural theory of performativity to critically analyze the common experience of family estrangement. We argue that professional discourse performatively constructs the functional family binary by equating ongoing, open, and positive family communication with functional family identity, while constructing estrangement as unnatural, dysfunctional, and in need of intervention. We then illustrate how some individuals who self-identify as estranged from a family member "trouble" the functional/dysfunctional family binary by articulating their own families as functionally estranged.